Posted by **Leslie** on Wednesday, February 17, 2010 at 7:09pm.

1.(Y+2)/(Y^2-9) * (4Y+12)/(3Y+6) ÷ 8/(2Y-6) =

2.(4X-Y)/(X+Y) * (X^2-Y^2)/(16X^2-Y^2) ÷ (2X-2Y)/(16X+4Y) =

3.(X^2-25)/(2X+12) * (X^2+8X+12)/(4X-20) ÷ (X^2+7X+10)/8X =

## Answer this Question

## Related Questions

- Algebra - There are two solutions to | 16x - 5 | = 3. The greatest solution is ...
- algebra - Solve the system by addition or substitution. 16x-4y=20 y=4x-4 I ask ...
- Math - 5(-3x - 2) - (x - 3) = -4(4x + 5) + 13 Answer Multiply factors. -15x - 10...
- algebra - x^2 +16x+64 x^2+16x=64 (x=3)^2=16x-64 16x=-64 x=-4 Check this problem ...
- math - The question is (2x+1)^2-2(2x^2-1) in simplest form Is this correct? [(2x...
- Pre-Calculus - Help please If f(x)=8x and g(x)=2x+1 find (fog)(x) 16x^2+8x 16x+1...
- Algerbra - how do you solve 7(3x+4)=8(2x+5)+13 expand the parenthesis...I will ...
- Math - find any stationary points of the function g(x) = (2x-3)square root of 5+...
- calc - find the derivative of y = sqrt(9 - 16x) Use the chain rule. First find ...
- math need asap - 5/8 x+1/16 x=11/16+x 16*(5/8 x+1/16 x) = 16(11/16+x) 80 + x + ...